2014
DOI: 10.1039/c4tc00399c
|View full text |Cite
|
Sign up to set email alerts
|

Interacting networks of purely organic spin–1/2 dimers

Abstract: In the present study we report the synthesis of some novel nitronyl nitroxide biradical systems 1-4c with various p-bridges between the radical centres. UV-Vis, IR, EPR and X-ray diffraction studies, along with MS and NMR data where appropriate, are described. Magnetic measurements revealed that the biradicals 1c, 3c and 4c exhibit a moderately strong antiferromagnetic intra-molecular exchange, whereas nitroxide 2c shows a significantly higher exchange coupling, which can only be explained by the presence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…These radical entities were chosen since they can be prepared without impurities after column chromatography and handled under air and ambient conditions. For scaling the intramolecular antiferromagnetic exchange interactions, several para‐phenylenyl‐bridged bis(nitronyl nitroxides) 1 – 4 were prepared and investigated by theoretical analysis and experimental magnetization experiments . Thus the influence of the bridging length on the intramolecular exchange interaction was elucidated (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These radical entities were chosen since they can be prepared without impurities after column chromatography and handled under air and ambient conditions. For scaling the intramolecular antiferromagnetic exchange interactions, several para‐phenylenyl‐bridged bis(nitronyl nitroxides) 1 – 4 were prepared and investigated by theoretical analysis and experimental magnetization experiments . Thus the influence of the bridging length on the intramolecular exchange interaction was elucidated (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the influence of the bridging length on the intramolecular exchange interaction was elucidated (Figure ). Here the distance of the central imidazolyl positions C2 to C2′ varied from 1.01 nm for the biphenyl spacer to 1.51 nm for the diphenyldiacetylene spacer …”
Section: Resultsmentioning
confidence: 99%
“…Serendipitously during the course of our study on organic biradical systems for the Bose-Einstein condensation we found the molecule BPNO (N,N'-([1,1'-biphenyl]-4,4'-diyl)bis(N-(tertbutylaminoxyl)) which exists in semi-quinoid form ( Figure 3). [27][28][29] At room temperature BPNO showed doublet EPR spectrum. Even after several purifications by column followed by repetitive crystallization no improvement in EPR spectrum was observed.…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the solvent, the prepared biradical crystallized in two different forms. [5] Earlier, we tested two nitronylnitroxides (NN) depicted as A [6,7] in Figure 1 and two iminonitroxides (IN) shown as B [8] with a tolane bridge (1,2-bis(phenyl) acetylene) for achieving 2D and 3D ordering of triplon excitations of these spin dimers in the crystal lattice.. Further, DFT calculations explained this phenomenon and indicated the advantage of Form I for further in-depth investigations.…”
mentioning
confidence: 98%
“…[3] Therefore a control of J intra as well as J inter is essential and we have shown earlier that this is possible in organic biradicals, where the intramolecular interactions can be fine-tuned through the applied spacer between the radical units. [5] Earlier, we tested two nitronylnitroxides (NN) depicted as A [6,7] in Figure 1 and two iminonitroxides (IN) shown as B [8] with a tolane bridge (1,2-bis(phenyl) acetylene) for achieving 2D and 3D ordering of triplon excitations of these spin dimers in the crystal lattice.. [5] Earlier, we tested two nitronylnitroxides (NN) depicted as A [6,7] in Figure 1 and two iminonitroxides (IN) shown as B [8] with a tolane bridge (1,2-bis(phenyl) acetylene) for achieving 2D and 3D ordering of triplon excitations of these spin dimers in the crystal lattice..…”
mentioning
confidence: 99%